Vinterudgravning i Braa - Andersen, Harald (Kuml, 1952)
The bronze cauldron from Braa In the village of Braa, southwest of Horsens, in February 1952, the remains were found of a huge bronze cauldron - a piece of imported Celtic work fashioned in the centuries immediately preceding the birth of Christ. It was undoubtedly an offering to the gods, as it had been broken into hundreds of pieces and placed in a pit dug to receive it. On top of it were Iaid two large boulders and a number of smaller stones. The cauldron had had a diameter of about 120 cms. and is therefore the largest metal container known from Denmark's prehistoric era. It has still not been assembled but, so far as can be judged, it was hemispherical in shape though narrowing slightly towards the rim. A massive iron ring was set around the rim and immediately beneath this were set three massive bronze handlemounts, curved and decorated with twining ornamentation and owl's heads. These mounts had held the iron ring-handles, which were covered with bronze and had pointed upwards, showing that the cauldron was designed to be hung up. It was probably incapable of standing on its thin baseplate. Five bulls' heads in bronze belong to the cauldron. Originally there must have been six, as it can be seen that the heads were placed in twos, one on each side of each of the three handles. The belly of the cauldron, of thin bronze sheeting, had been riveted to a short neck. A number of fragments of leather, found together with the pieces of bronze, have still not been explained, but they appear in some way to have been positioned upon the outer surface of the cauldron. Nor has a place yet been found for the figure of a bird - it is possible that it did not belong to the cauldron. Together with the cauldron was found an iron axe. Several cauldrons of a somewhat similar type have been found in Denmark. The best known is the large silver cauldron from Gundestrup peat-bog in Himmerland. The Braa cauldron will be preserved at the Prehistoric Museum in Aarhus. Harald Andersen